Removal of minocycline from high concentrated aqueous medium by nonliving and lipid-free Chlorella sp. biomass (2021)
This work evaluated the removal of minocycline (MC) by the nonliving Chlorella sp. biomass (NLB) and modified by a lipid extraction procedure (LEB). Both biomasses have different morphology (NLB: globular-like; LEB: flakes and blocks) and size distribution. The pH showed a significant synergistic influence on MC removal (p < 0.05). MC initial concentration (C0) and biomass dosage significantly interact, suggesting that LEB agglomeration decreased removal. NLB removed 90.8 ± 1.3% of MC and LEB 80.8 ± 1.4% at C0 = 53.89 mg/L, 50 mg of biomass and pH 10. The adsorption kinetics and isotherms suggested multilayer formation by physical and chemical adsorption on heterogeneous and macroporous surfaces. According to results, NLB as an adsorbent had an economic disadvantage because of production costs despite good removal efficiency. However, it is possible to take advantage of the biomass after removing value-added compounds (LEB) as a zero-waste strategy.